Reversible photoswitching of the interfacial nonlinear optical response - Schulze, Michael; Utecht, Manuel; Hebert, Andreas; Rück-Braun, Karola; Saalfrank, Peter; Tegeder, Petra (The journal of physical chemistry letters, 2015)
Incorporating photochromic molecules into organic/inorganic hybrid materials may lead to photoresponsive systems. In such systems, the second-order nonlinear properties can be controlled via external stimulation with light at an appropriate wavelength. By creating photochromic molecular switches containing self-assembled monolayers on Si(111), we can demonstrate efficient reversible switching, which is accompanied by a pronounced modulation of the nonlinear optical (NLO) response of the system. The concept of utilizing functionalized photoswitchable Si surfaces could be a way for the generation of two-dimensional NLO switching materials, which are promising for applications in photonic and optoelectronic devices.